PERCEPTION OF USING TIKTOK TO IMPROVE VOCABULARY MASTERY ON ELEVENTH GRADE STUDENTS AT SMA NEGERI 3 BAUBAU - Nety Nety; Nining Syafitri; Siti Rahma Dina Ismail (English Education Journal, 2023)
The problem statement of this research is whether the Tiktok application give an impact to improve students English vocabulary masery in SMA Negeri 3 Baubau of eleventh grade students. The research provides the motivation to explore students’ perceptions of the influence of the students' use of social media such as TikTok on the development of the student's English vocabulary on 11th grade students in SMA Negeri 3 Baubau. This research used a mixed methods with QUAL-quan type, where data will be distributed by qualitative methods such as interviews and documentaries and quantitative methods such as questionnaires. A total of 37 11th graders, 3 baubau students, have been involved in the research. The technique of data Analysis used embendded design with chosee data collecting, data reduction, data display, and data conclution. Results showed that social media TikTok provided English sources of content that could be used to supplement the student's English vocabulary. Students can also access applications at any time and anywhere, further students can also gain entertainment and add their English vocabulary at any one time. Beyond that students also mention the problems they face in accessing a ticktock app such as an Internet connection. It may be concluded that students have a positive perception of a TikTok application with a view to improving the English vocabulary